Toxoplasma GRA15 Activates the NF-κB Pathway through Interactions with TNF Receptor-Associated Factors - Lamba Omar Sangaré (American Society for Microbiology, 2019)
ABSTRACT The protozoan parasite Toxoplasma gondii secretes proteins from specialized organelles, the rhoptries, and dense granules, which are involved in the modulation of host cell processes. Dense granule protein GRA15 activates the nuclear factor kappa B (NF-κB) pathway, which plays an important role in cell death, innate immunity, and inflammation. Exactly how GRA15 activates the NF-κB pathway is unknown. Here we show that GRA15 interacts with tumor necrosis factor receptor-associated factors (TRAFs), which are adaptor proteins functioning upstream of the NF-κB transcription factor. We identified several TRAF binding sites in the GRA15 amino acid sequence and showed that these are involved in NF-κB activation. Furthermore, a TRAF2 knockout cell line has impaired GRA15-mediated NF-κB activation. Thus, we determined the mechanism for GRA15-dependent NF-κB activation. IMPORTANCE The parasite Toxoplasma can cause birth defects and severe disease in immunosuppressed patients. Strain differences in pathogenicity exist, and these differences are due to polymorphic effector proteins that Toxoplasma secretes into the host cell to coopt host cell functions. The effector protein GRA15 of some Toxoplasma strains activates the nuclear factor kappa B (NF-κB) pathway, which plays an important role in cell death, innate immunity, and inflammation. We show that GRA15 interacts with TNF receptor-associated factors (TRAFs), which are adaptor proteins functioning upstream of the NF-κB transcription factor. Deletion of TRAF-binding sites in GRA15 greatly reduces its ability to activate the NF-κB pathway, and TRAF2 knockout cells have impaired GRA15-mediated NF-κB activation. Thus, we determined the mechanism for GRA15-dependent NF-κB activation.